Whole Blood Cytokine Response to Local Traffic-Related Particulate Matter in Peruvian Children With and Without Asthma - Negherbon, Jesse P.; Romero, Karina; Williams, D’Ann L.; Guerrero-Preston, Rafael E.; Hartung, Thomas; Scott, Alan L.; Breysse, Patrick N.; Checkley, William; Hansel, Nadia N. (Frontiers in Pharmacology, 2017)
This study sought to investigate if acute phase immune responses of whole blood from Peruvian children with controlled and uncontrolled asthma differed from children without asthma, following exposure to traffic-related particulate matter (TRPM). TRPM, including particulate matter from diesel combustion, has been shown to stimulate acute airway inflammation in individuals with and without asthma. For this study, a whole blood assay (WBA) was used to test peripheral whole blood samples from 27 children with asthma, and 12 without asthma. Participant blood samples were stimulated, ex vivo, for 24-h with an aqueous extract of TRPM that was collected near study area highways in Lima, Peru. All participant blood samples were tested against the same TRPM extract, in addition to purified bacterial endotoxin and pyrogen-free water, which served as positive and negative WBA controls, respectively. The innate and adaptive cytokine responses were evaluated in cell-free supernatants of the whole blood incubations. Comparatively similar levels were recorded for nine out of the 10 cytokines measured [e.g., – Interleukin (IL)-1β, IL-6, IL-10], regardless of study participant asthma status. However, IL-8 levels in TRPM-stimulated blood from children with uncontrolled asthma were diminished, compared to subjects without asthma (633 pg/ml vs. 1,023 pg/ml, respectively; p < 0.01); IL-8 responses for subjects with controlled asthma were also reduced, but to a lesser degree (799 pg/ml vs. 1,023 pg/ml, respectively; p = 0.10). These relationships were present before, and after, adjusting for age, sex, obesity/overweight status, C-reactive protein levels, and residential proximity to the study area’s major roadway. For tests conducted with endotoxin, there were no discernible differences in cytokine response between groups, for all cytokines measured. The WBA testing conducted for this study highlighted the capacity of the TRPM extract to potently elicit the release of IL-8 from the human whole blood system. Although the small sample size of the study limits the capacity to draw definitive conclusions, the IL-8 responses suggest that that asthma control may be associated with the regulation of a key mediator in neutrophil chemotaxis, at a systemic level, following exposure to PM derived from traffic-related sources.